Inheritance of anthracnose resistance to Colletotrichum lindemuthianum race 69 in common bean genotype PI 207262 - Poletine, Juliana Parisotto; Vidigal, Maria Celeste Gonçalves; Vidigal Filho, Pedro Soares; Scapim, Carlos Alberto; Silvério, Lucas (Acta Scientiarum. Agronomy, 2008)
Common bean (Phaseolus vulgaris L.) cultivar PI 207262, resistant to Colletotrichum lindemuthianum race 69, was crossed with cultivars Michelite and Perry Marrow (susceptible to the race), Dark Red Kidney, Cornell 49242, AB 136 and G 2333 (resistant to it) and F1 and F2 generations were obtained under greenhouse conditions. The 15-day-old plants were inoculated using 1.2 x 106 spores/ml water spore suspension. The reaction of F1 and F2 populations showed that Dark Red Kidney, Cornell 49242 and AB 136 cultivars have respectively the dominant resistance genes A (Co-1), Are (Co-2) and Q (Co-6). The results indicated the segregation of three dominant resistance genes, two of them present in G 2333 (Co-5 and Co-7) and another present in PI 207262, which is located in Co-4 locus. In this experiment it was not possible to distinguish gene Co-42 in G 2333 cultivar from gene Mexique 2 (Co-4) in PI 207262, because they are located in the same locus, which makes identification using traditional screening methods possible.